Final Cut Pro X Guru: Advanced Trimming. - Harauz, Nick (linkedin.com, 2016)
Discover advanced trimming techniques in Final Cut Pro X. Explore extending edits, connected clips, comparing cuts, using numeric and dynamic trimming, and more.